Macro-event recognition in healthy aging, Alzheimer's disease, and mild cognitive impairment [Data] - Kokje, Eesha; Gerwien, Johannes; Stutterheim, Christiane von (Universität, 2021)
The data set contains the data associated with the study on "Macro-event recognition in healthy aging, Alzheimer's disease, and mild cognitive impa...
Gesehen am 10.03.2022
Keywords: Forschungsdaten; Datenbank